2017
DOI: 10.1007/s13320-017-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of high sensitivity eight-element multiplexed fiber laser acoustic pressure hydrophone array and interrogation system

Abstract: Fiber laser hydrophones have got widespread concerns due to the unique advantages and broad application prospects. In this paper, the research results of the eight-element multiplexed fiber laser acoustic pressure array and the interrogation system are introduced, containing low-noise distributed feedback fiber laser (DFB-FL) fabrication, sensitivity enhancement packaging, and interferometric signal demodulation. The frequency response range of the system is 10 Hz -10 kHz, the laser frequency acoustic pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Recently, researchers in Russia have reported a hydrophone used in their towed array, but the acoustic pressure responsivity is not a flat pattern from 20 Hz to 495 Hz [72]. In contrast, a report from China has shown that the acoustic sensitivity is about 115 dB re Hz/Pa between 10 Hz and 10 kHz for their DFB FL-style FOH, which has improved the very-low-frequency detection ability compared with other designs [73]. The researchers from National University of Defense Technology (NUDT) have also investigated very-low-frequency interferometric FOH with a sensitivity of -116 dB re rad/μPa between 10 Hz and 2 kHz, phase noise of -102 dB re rad/Hz 1/2 @100 Hz, and equivalent noise pressure of 14 dB @100 Hz re μPa/Hz 1/2 , as shown in Figs.…”
Section: Very-low-frequency Detection Of Fohmentioning
confidence: 98%
“…Recently, researchers in Russia have reported a hydrophone used in their towed array, but the acoustic pressure responsivity is not a flat pattern from 20 Hz to 495 Hz [72]. In contrast, a report from China has shown that the acoustic sensitivity is about 115 dB re Hz/Pa between 10 Hz and 10 kHz for their DFB FL-style FOH, which has improved the very-low-frequency detection ability compared with other designs [73]. The researchers from National University of Defense Technology (NUDT) have also investigated very-low-frequency interferometric FOH with a sensitivity of -116 dB re rad/μPa between 10 Hz and 2 kHz, phase noise of -102 dB re rad/Hz 1/2 @100 Hz, and equivalent noise pressure of 14 dB @100 Hz re μPa/Hz 1/2 , as shown in Figs.…”
Section: Very-low-frequency Detection Of Fohmentioning
confidence: 98%
“…Several research on techniques for extending the dynamic range of FOHs has been reported, mostly on theoretical analysis and estimation of the dynamic range of FOHs. Various signal detection schemes and corresponding optimization methods have been investigated [3][4][5][6]. Among these, heterodyne detection techniques have received attention and research, showing excellent performance in the dynamic range [7][8][9].…”
mentioning
confidence: 99%